Membentuk Karakter Religius dengan Pembiasaan Perilaku Religi di Sekolah: Studi di SMA Negeri 3 Ponorogo - Lyna Dwi Muya Syaroh; Zeni Murtafiati Mizani (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
This research begins with the anxiety of the national character and culture problems. Recognized or not, there are currently many real and worrying crises in society involving students as the next generation of the nation. Islamic Religious Education which ideally teaches the values ​​of goodness, one of which is religiosity, which when these values ​​are internalized to students, of course deviations can be avoided. The purpose of this study is to analyze the implementation of the habituation method, constraints, and solutions encountered in implementing the habituation method to shape students' religious character. This research method uses a qualitative descriptive approach and the type of research is a case study. Data collection techniques include observation, interview and documentation. Data analysis techniques using Miles and Huberman with the steps of data collection, data reduction, data display, and drawing conclusions. The results of the study found that: (1) Implementation of the habituation method in shaping the religious character of class students through prayer before learning and before going home, reading short letters in juz'amma and verse verses, chanting asma'ul husna, dhuha prayer, dzuhur prayer and asar congregation, Friday prayers and Friday blessings, Friday infaq, khatmil al-Qur'an, khatib and PHBI (Commemoration of Islamic Holidays); (2) Constraints faced in implementing the habituation method in shaping students 'religious character are influenced by two factors namely: internal factors including innate behavior and external factors including lack of maximum conditioning and support from teachers, students' educational backgrounds, different parenting , peers, social media and infrastructure; (3) The solution to overcome the constraints of implementing the habituation method in shaping students' religious character is by socializing the importance of character education, discipline, reward and punishment, controlling, and adding facilities and infrastructure.This research begins with the anxiety of the national character and culture problems. Recognized or not, there are currently many real and worrying crises in society involving students as the next generation of the nation. Islamic Religious Education which ideally teaches the values ​​of goodness, one of which is religiosity, which when these values ​​are internalized to students, of course deviations can be avoided. The purpose of this study is to analyze the implementation of the habituation method, constraints, and solutions encountered in implementing the habituation method to shape students' religious character. This research method uses a qualitative descriptive approach and the type of research is a case study. Data collection techniques include observation, interview and documentation. Data analysis techniques using Miles and Huberman with the steps of data collection, data reduction, data display, and drawing conclusions. The results of the study found that: (1) Implementation of the habituation method in shaping the religious character of class students through prayer before learning and before going home, reading short letters in juz'amma and verse verses, chanting asma'ul husna, dhuha prayer, dzuhur prayer and asar congregation, Friday prayers and Friday blessings, Friday infaq, khatmil al-Qur'an, khatib and PHBI (Commemoration of Islamic Holidays); (2) Constraints faced in implementing the habituation method in shaping students 'religious character are influenced by two factors namely: internal factors including innate behavior and external factors including lack of maximum conditioning and support from teachers, students' educational backgrounds, different parenting , peers, social media and infrastructure; (3) The solution to overcome the constraints of implementing the habituation method in shaping students' religious character is by socializing the importance of character education, discipline, reward and punishment, controlling, and adding facilities and infrastructure.